INTERAKSI VERBAL ANTARA GURU DAN SISWA KELAS VI SD GMIM 31 MANADO DAN PENGARUHNYA PADA MOTIVASI SISWA - SUMAMPOW, RIDEL EFRAIM; TULUNG, GOLDA J.; RATTU, JULTJE A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research is entitled â€œVerbal Interaction between Teacher and Students of the Sixth Grade of SD GMIM 31 MANADO and Its Influences on the Studentsâ€™ Motivationâ€. In this research, the writer focuses on verbal interactions that occur between teacher and students in the classroom and how the interaction influence on studentsâ€™ motivation. The aims of this research are to identify and classify the kinds of verbal interaction occuring between teacher and stdents in the classroom as well as to analyze how the interaction influences studentsâ€™ motivation. In this research, the writer uses qualitative method with case study. To analyze several kinds of verbal interactions that occur between teacher and students in the class, the writer uses theory of FIAC by Flanders (1963). Interviews were conducted to find out whether verbal interactions influence studentâ€™s motivation. The results of this research show 8 categories of interaction that occur in the class; acceptance of feelings, praising or encouragement, asking questions, lecture, giving directions, criticizing or justifying, response, silent or confusions. In addition, the results of interview show that the interaction influences student motivation in these ways: 1) students like to learn English, 2) students can read in English, 3) students can write in English, 4) students can speak in English, 5) students can listen in English, 6) students understand what the teacher teaches when learning English, 7) the way of teacher to teach is fun for students, 8) teacher often use English when teaching, 9) what is interesting about English, 10) internal interaction class when the learning process between teacher and student motivates the student.Â Â Â Â Â  Key Words: Interaction, Studentsâ€™ Motivation